How Bureaucratic Representation Affects Public Organizational Performance: A Meta‐Analysis. (4th April 2021) - Ding, Fangda; Lu, Jiahuan; Riccucci, Norma M.
Abstract : Abstract: The impact of representative bureaucracy on public organizational performance has received a good deal of attention in public management. However, the literature provides little systematic rationalization about the effects of the individual constructs of representative bureaucracy on organizational performance. This meta‐analysis of 648 effect sizes from 80 quantitative studies, closely examines the conditions under which bureaucratic representation affects public organizational performance. The research provides evidence on the relationship between different constructs of representative bureaucracy and organizational performance. This meta‐analysis overall advances the theory of representative bureaucracy from several perspectives. It shows that the effects of representative bureaucracy on public organizational performance are positive in general, but that these effects are moderated by several contextual factors. And our finding that the effects of bureaucratic representation on public organizational performance was shaped by demographics and types of representation, levels of bureaucracy, and performance measurements adds to the micro‐theory behind individual bureaucratic actions .